Numerical investigation on the evolutionary characteristics of landslide dam-break flow in a wet-bed channel with riparian vegetation - Song, Gangyong; Chen, Yong; Zhao, Penghui; Yuan, Hao (Frontiers in Marine Science, 2024)
Riparian vegetation always grows on both sides of a natural river during a dam-break event, while the river typically retains some water instead of completely drying out. The RNG k-ϵ turbulence model is employed to examine the evolutionary characteristics of the dam-break flow in the downstream vegetated channel. This model facilitates the analysis of water-level fluctuations, velocity distributions, and the retardation effects of vegetation on the dam-break flow by varying the initial water depth (IWD) in the downstream channel. Results indicates that as the water depth in the downstream channel increases, the dam-break wave tends to form more readily, possesses a larger amplitude, and the duration of rapid congestion in the dam-break current decreases. Hence, the surface velocity gradually declines and shows an intermittent distribution. Vegetation impedes the flow evolution in the vegetated area, an effect that diminishes progressively with increasing IWD. In contrast, vegetation hastens the evolution of water flow in the main channel, which remains minimally affected by the IWD.